COMMUNICATIVE COMPETENCE BASED ENGLISH SYLLABUS DESIGN FOR STUDENTS OF PTKI (PERGURUAN TINGGI KEAGAMAAN ISLAM) - Rosyida, Ulva Fatiya (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2019)
ABSTRACTCommunicative Competence (CC) is the target of language teaching today. It contains six competences: Linguistic Competence, Discourse Competence, Socio-Cultural Competence, Formulaic Competence, Interactional Competence, and Strategic Competence. Teaching English for students of PTKI should also convey those competences. The competences should be applied in the syllabus, the materials, etc. However, most of the English syllabus has not conveyed the highlight of those competences. This paper, therefore, aims to propose a syllabus design and the sample of materials based on Communicative Competence. The syllabus contains the highlight of those competences for each topic. The design, then, can be developed by the lecturers to meet the students? needs.